THE ROLE OF TRANSFER EXPENDITURE IN PROVIDING INCOME DISTRIBUTION - Mehmet Sadık AYDIN (Fırat University, 2019)
The provision of justice in income distribution is considered one of the most basic tasks of the state. One of the most basic examination topics in the history of economic thought is providing justice in income distribution. The controversial literature on state functions is also felt in the distribution of income. The state sometimes tries to provide justice in income distribution through income policies and sometimes through expenditure policies. Income policy instruments usually consist of taxes. This instruments consist of progrresive taxation, seperationg principles and minimum living allowences. The state is influencing the indicators in the economy by different types of expenditure. Moreover, it can not be said that all expenditures the state has made serve justice in the distribution of income. On the contrary, it is also known that some expenditures lead to unfairness in income distribution. The portion of income distribution related to expenditures is mostly made through transfer expenditures. While social transfers make income distribution more equitable, interest payments from financial transfers cause injustice in redistribution. In this study, after 2006, a new system in the budget will be transformed in Turkey, and the expenditure policies for providing justice in income distribution will be analyzed. Since the actual transfers take place in the form of interest payments and social security payments even though there are transfers other than financial and social transfers, only these two issues will be addressed in the study. As a result of the study, policy proposals will be made on whether the requirements of the social state specified in the Constitution have been fulfilled and on which the solution should be made.